DETECTION OF THE PEPTIDE P17-1 (HIV) BY SURFACE ENHANCE RAMAN SCATTERING (SERS) - Carneiro, Leandro B. [UNESP]; Moraes, Marli L.; Ribeiro, Sidney J. L. [UNESP]; Brolo, Alexandre G. (Soc Brasileira Quimica, 2019)
A bioanalytical method for HIV detection based on surface-enhanced Raman scattering (SERS) is described. The assay targeted the peptide p17-1. This peptide sequence is present in the protein p17, a structural protein essential in the life cycle of the human immunodeficiency retrovirus (HIV). The antibody anti-p17 was immobilized in a planar gold surface using self-assembled techniques. This planar platform was used to capture the target analyte (p17-1 peptide). The peptide detection was carried out using specially designed SERS probes, consisting of gold nanoparticles coated with a Raman reporter molecule (Nile Blue A) and functionalized with anti-p17. This sandwich assay led to the successful detection of the peptide p17-1 at 40.8 ng/mL levels. The sandwich assay described here demonstrated that the SERS technique can rival more common fluorescence methods, such as ELISA, in the detection HIV-type virus.
Keywords: HIV; SERS; peptide p17-1; SERS probes; SERS Immunoassay